Respostas

2014-07-14T04:20:17-03:00
A) x² = 7x - 12

x² - 7x + 12 = 0
soma -> 7        x1 = 3
produto -> 12    x2 = 4

B) 2x(4x - 1) = 21

8x² - 2x - 21 = 0
Δ = b² - 4.a.c 
Δ = (-2)² - 4.8.(-21)
Δ = 4 + 672
Δ = 676

Raiz de Δ = 26 


x1 = (-b + √ Δ)/2a = (2+26)/16 = 28/16 = 7/4 

x2 = (-b - √ Δ)/2a = (2-26)/16 = -24/16 = -3/2

C) (3x + 1)² + (x - 2).(x + 1) = -1

9x² + 1 + (x² + x - 2x + 2) + 1 = 0
9x² + x² + x - 2x + 1 + 2 + 1 = 0
10x² - x + 4 = 0

Δ = b² - 4.a.c
Δ = (-1)² - 4.10.4
Δ = 1 - 160
Δ = -159
Δ não existe